The Mediating Role of Goal Setting in the Relationship Between Creative Thinking and Academic Hope - Khalooaskari, Hossein; Barzegar , Majid; Sohrabi Shegefti, Nadereh; javidi , Hojatollah (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The aim of this study was to investigate the mediating role of goal setting in the relationship between creative thinking and academic hope. Methods and Materials: In this correlational study, from the population of male first and second grade students in Kazeroon, 266 participants were selected using multi-stage cluster sampling from the cities of Kazeroon, Khesht, Kenartakhteh, Baladeh, and Jarreh. To achieve the research objectives, standardized questionnaires on goal setting, academic hope, and creative thinking were used, with Cronbach’s alpha coefficients of 0.97, 0.93, and 0.98, respectively. Findings: The goodness of fit index with a value of 0.603 confirmed the overall model fit. Goal setting, with a total path coefficient of 0.154, influenced the relationship between creative thinking and academic hope using the bootstrap approach in the partial least squares method. Conclusion: This study aimed to explore the mediating role of goal setting in the relationship between creative thinking and academic hope among high school students. The findings revealed significant relationships between these variables, supporting the proposed hypotheses and aligning with previous research.